Advancements in surgical education: exploring animal and simulation models in fetal and neonatal surgery training - Davidson, Emily L.; Penniston, Kristina L.; Farhat, Walid A. (Frontiers in Pediatrics, 2024)
The use of animal models in surgical training has a long history, dating back to Halsted's introduction in 1889. These models, often utilizing large animals like swine and dogs, offer valuable insights into fetal and neonatal surgeries. They allow for the study of long-term outcomes and the simulation of various diseases and anomalies, providing essential training experiences not readily available in human surgeries. However, there are notable limitations, including anatomical and physiological differences from humans, ethical considerations, and substantial infrastructure and maintenance costs. Simulation-based training offers several benefits, including standardized and safe learning environments without risks to real patients. Bench models, using synthetic materials or non-living animal tissue, provide cost-effective options for skills development. Virtual reality and 3-D printing technologies further enhance simulation experiences, allowing for the replication of complex clinical scenarios and patient-specific anatomies. While these models offer significant advantages, they lack the complexity of biological systems found in animal models. In conclusion, both animal and non-animal simulation models play crucial roles in enhancing surgical education, particularly in fetal and neonatal surgery. While advancements in non-animal technologies are important for ethical reasons, the continued necessity of animal models in certain areas should be acknowledged. By responsibly integrating these models into training programs, surgical education can be further enriched while upholding ethical standards and ensuring optimal patient outcomes.